Analisis Manajemen Kolaboratif Model Pentahelix Sebagai Strategi Pengelolaan Objek Wisata Pemandian Air Panas Desa Sumberarum Kabupaten Magelang - Amalia Nessa Arlinda; Ayuk Yuliana; Taufiq Khaerudin; Zulfatun Nisa’; Bondan Nugroho; Diah Agustina Prihastiwi (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research is motivated by the lack of availability of facilities and infrastructure, competition between managers and lack of human resources in the management of tourism objects. The location of this bathhouse is located in Dimajar Hamlet, Sumberarum Village, Tempuran District, Magelang Regency. The formulation of this research problem is how to analyze the application of the Pentahelix Model Collaborative Management as a Tourism Object Management Strategy in the Hot Springs of Sumberarum Village, Magelang Regency. This research uses the theory of strategic management from Fred R David (2004). By using SWOT analysis technique (Strengths, Weakness, Opportunities, Treaths) and with qualitative descriptive method. The results showed that Sumberarum Village has the strength to advance the tourism sector through the utilization of its natural resources, hot springs as the main attraction as a Hot Springs Tourism Object in Sumberarum Village. Meanwhile, the weakness is the human resources involved from among the local residents or residents of Sumberarum Village, still have limitations both in terms of quality and quantity. In addition, the management system of this tourist attraction is also not well structured so that it can affect the success of achieving organizational goals. The existence of the Sumberarum Village Hot Springs Tourism Object opens up extensive opportunities for local residents to create new jobs. The number of hot springs in Sumberarum Village is a threat in the competition for the management of hot spring tourism objects in the area due to the location of tourist objects that are close to each other. The suggestions of this research are (1) increasing the human resources involved (2) improving the structured tourist attraction management system (3) opening up jobs for residents around tourist objects (4) increasing unique innovations and maintaining cooperation between stakeholders.